Can vessel sea chest design improve fouling control coating performance?. (15th July 2022) - Piola, Richard; Grandison, Clare; Shimeta, Jeff; del Frate, Alex; Leary, Martin
Abstract: Sea chests are arguably the most problematic vessel niche areas with respect to managing and preventing marine biofouling. This is partly due to the design and location of these structures, as well as the difficulty in managing them with conventional antifouling technologies. Antifouling coatings are typically designed for use on flat exposed hull surfaces that experience predictable flow conditions, and often perform poorly under variable flow conditions found in sea chest environments. This study examined whether custom-designed inserts retrofitted to experimental sea chests to alter their internal geometry and flow characteristics could improve antifouling coating performance. For in-laboratory sea chests coated with self-polishing copolymer (SPC) antifouling coatings, retrofitted inserts improved the polishing rate and erosion consistency of the coating; likely due to enhanced laminar flow and greater uniform wall shear stress over the surface of the sea chest, and the elimination of circulation zones and/or pockets of static water. For in-field sea chests coated with fouling-release coatings, inserts had little direct impact on biofouling accumulation compared to unmodified sea chests, with similar levels of fouling recorded per cm 2 of sea chest surface. Inserts did however reduce the overall biomass of biofouling accumulated, through a reduction in available settlement area. Highlights: Sea chests are one of the most problematic vessel niche areas for marine biofouling. Typical sea chest designs are not favourable to good antifouling coating performance. Modifying sea chest with inserts significantly improved SPC coating polishing rates. Improved coating polishing is due to enhanced laminar flow and wall shear stress. Rethinking vessel sea chest design may control biofouling in this niche area.